Optimization of Cutting Parameters for Surfaces Roughness of Medium Carbon Steel C-45 in CNC Turning Machining by Using Taguchi Method - Salem. A. Sultan; Samir S. Abubaker; .Abdarazag A; Hassan, Salah Iddin A. S. Issa (Surman Journal of Science and Technology, 2021)
The objective of this study is to optimize the Computer Numerical Control machine (CNC) turning parameters that gives the fine surface finish for the parts that made of medium carbon steel C45 using carbide cutting tool (coated insert cemented carbide) which have high resistance of deflection, wear and fraction on CNC turning operation with coolant. The surface finish quality is one of the most specified requirements in the machining process. To obtain the optimal surface finish, the Taguchi method used for optimization of the turning experiments based on a full factorial design, to determine three different parameters and levels by using orthogonal arrays, 9 experiments were obtained. Choice of three parameters (feed rate, cutting speed and depth of cut) were important, the cutting parameters were selected as follow: Feed rate (0.075, 0.100, 0.125mm), cutting speed (166.24, 180.70, 197.32 mm/min), depth of cut (0.5, 0.75, 1.0 mm) these parameters were chosen according to SANDVIC Tool Manufacturing Company. The series of turning experiments were performed to measure the surface roughness. The MINITAB Statistical Software was used to calculate the signal-to-noise ratio (S/N), and analysis of the variance (ANOVA), the best optimal levels and the effect of the process parameters on surface roughness were obtained. The parameters for experiment surface roughness were the feed (0.075mm/rev), cutting speed (180.70 mm/min), depth of cut (3.0mm) and that conducted in experiment number five (5). A conformation of experiment to obtained optimal levels of process parameters was carried out in order to demonstrate the effectiveness and efficiency of the employed Taguchi method as a tool to measure surface roughness.